5 - Dispute Resolution and Electoral Justice in Africa: The Way Forward - Nkansah, Lydia Apori (Africa Development, 2021)
This article examines electoral adjudication in Africa’s democratisation process. The idea of aggrieved persons instituting an election petition in court as opposed to resorting to violence is a positive sign in Africa’s democratisation process. The aggrieved are choosing the law as their arbiter. This practice will facilitate the institutionalisation of succession and entrench the rule of law and constitutionalism. However, there have been misgivings about the outcome of judicial adjudication of some of these electoral disputes. Electoral disputes are not always resolved expeditiously and courts’ decisions on such matters are sometimes overtaken by events. There is also the perception of judicial bias in some cases. In the same way the large numbers of election petitions put a lot of strain on the judiciary, clogging up the courts. Voter education on realistic expectations of elections by citizens should be intensified so that an election ends with the ballot and only genuine cases go through adjudication.